Foucault for Architects. - Fontana-Giusti, Gordana (Thinkers for architects, 2013)
From the mid-1960s onwards Michel Foucault has had a significant impact on diverse aspects of culture, knowledge and arts including architecture and its critical discourse.?The implications for architecture have been wide-ranging.?His archaeological and genealogical approaches to knowledge have transformed architectural history and theory, while his attitude to arts and aesthetics led to a renewed focus on the avant-garde. Prepared by an architect,?this book offers an excellent entry point into the remarkable work of Michel Foucault, and provides a focused introduction suitable.